Prosedur Pengoperasionalan Pengadaan Barang Dan Jasa pada PT. Kereta Api Indonesia (Persero) DAOP VIII Surabaya - Rangga Dwi Darmawan; Siti Ning Farida (Pusat Riset dan Inovasi Nasional, 2024)
This article aims to study the Operational Procedures for Procurement of Goods and Services at PT. Kereta Api Indonesia (Persero) DAOP VIII Surabaya is carried out by understanding and getting to know the work environment and involving direct understanding and practice regarding the Work Plan and Requirements (RKS), Procurement Implementation Order (SP3), Aanwizjing, Tenders, Negotiations, and so on . Goods and Services Procurement Activities at PT. Kereta Api Indonesia DAOP 8 is a process for obtaining goods or services by ministries/institutions/regional work units/other institutions, starting from needs planning to completing all stages of obtaining goods or services. Procurement of goods or services carried out by PT. Kereta Api Indonesia DAOP 8 has a significant role in supporting national development and improving public services in various regions.